146 Early life microbial exposures and disruptions shape subsequent animal health. (7th December 2018) - Willing, B
Abstract: Over the past decade it has become clear that factors affecting early life microbiota, such as antibiotic exposure, contribute substantially to immune and metabolic diseases, including asthma, diabetes and obesity in human populations. While it is unlikely that pigs will start needing inhalers, it is naïve to expect that early life antibiotic and other microbiome-influencing factors are not important to the ability of an animal to tolerate a pathogen or metabolic challenge later in life. Our studies in the pig have demonstrated that early life antibiotic exposure result in altered development of the pancreas, resulting in evidence of insulin resistance long after antibiotic withdrawal. Early life antibiotic exposures also had long-term consequences on functionality of the immune system resulting in an altered ability to tolerate a Salmonella challenge. In this presentation I will discuss the many factors affecting the early life microbiota and the evidence indicating the need to shape early life microbial exposures so as to optimize long-term animal health.